SINKRONISASI ESTRUS DENGAN IMPLANT CONTROLLED INTERNAL DRUG RELEASE INTRAVAGINA PADA KAMBING PERANAKAN ETTAWA - Kresno Suharto; Eko Marhaeniyanto (BUANA SAINS, 2010)
This research was conducted at Field Laboratory of BPT-HMT Singosari Malang. The objectives of current research were to identifity respond, onset and duration of female Etawah crossbreed goat estrus in estrus phase. Eight female Etawah crossbreed goats with live weight of 32.5  2.5 kg were used in this research which feed with 3 kg King Grass and 1 kg concentrate in a day during the research. In order to estrus synchronization, intravagina Controlled Internal Drug Release (CIDR) was implanted in female Etawah crossbreed, then injecting with PGF2. Method used in current research was experimental with purposive sampling. Parameters used in this research were : 1) respond estrus, 2) onset estrus, 3) duration estrus. The results on estrus synchronization used implanted of intravagina Controlled Internal Drug Release (CIDR) showed that respond, onset and duration of female Etawah crossbreed estrus gave a respond estrus of 100% with normal estrus cycle